Measurement of Bs0 Mixing Parameters from the Flavor-Tagged Decay Bs0→J/ψ - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
From an analysis of the flavor-tagged decay Bs0→J/ψ we obtain the width difference between the Bs0 light and heavy mass eigenstates, ΔΓs=0.19±0.07(stat)-0.01+0.02(syst)ps-1, and the CP-violating phase, s=-0.57-0.30+0.24(stat)-0.02+0.08(syst). The allowed 90% CL intervals of ΔΓs and s are 0.06<ΔΓs<0.30ps-1 and -1.20<s<0.06, respectively. The data sample corresponds to an integrated luminosity of 2.8fb-1 accumulated with the D0 detector at the Fermilab Tevatron collider. © 2008 The American Physical Society.
Keywords: Collider; Data samples; Eigen states; Fermilab Tevatron; Integrated luminosities